A study of isokinetic strength and laxity with and without anterior cruciate ligament injury - Kim, Kewwan (J Phys Ther Sci, 2016)
[Purpose] The purpose of this study was to provide useful information for future treatments and to organize rehabilitation programs for anterior cruciate ligament injury by assessing isokinetic muscle strength and laxity of knee joints in athletes with anterior cruciate ligament injuries. [Subjects and Methods] Thirty-one high school athletes with anterior cruciate ligament injuries participated in this study. Isokinetic muscle strength at 60°/sec and anterior cruciate ligament laxity for non-involved and involved sides, classified on the basis of the severity of anterior cruciate ligament injury, were assessed. [Results] A comparison of isokinetic muscle strength measured from the non-involved and involved sides showed a significant difference in the maximum strength and knee flexor muscle strength. For laxity, a significant difference was observed in the anterior drawer test results obtained with a force of 88 N. [Conclusion] In conclusion, this study has shown that the assessment of isokinetic muscle strength and ligament laxity from athletes with anterior cruciate ligament injury should be utilized to provide baseline data for prevention and prediction of injury.